The Effect of the Guided Discovery Learning Model on Critical Thinking Skills in IPAS Learning - Andi Aryadi; Dewi Hartini; Muhammad Ilham (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
The problem underlying this research is the low critical thinking skills of students. This research was conducted at SD Negeri 03 Maros using a quantitative approach. The type of research used is a quasi-experimental design with a non-equivalent control group design. The research population was all fifth grade students of SD Negeri 03 Maros in the 2025/2026 academic year. Sampling in this study was non-probability sampling using saturated sampling techniques. Data collection techniques in the form of tests and hypothesis testing used were the Independent Sample Test. The results of the research conducted on the independent sample test obtained a sig. value of 0.000 <0.05 and a calculated t value of 10.045> 2.0017 t table so it was concluded that there was a significant difference in critical thinking skills between students taught using the Guided Discovery Learning model and students taught using the direct learning model.